Certification Process of Starlink Wifi on A320 Aircraft - Malau, Roni Hasudungan; Mulyanto, Taufiq; Imam Nurhakim, Muhamad Luthfi (Politeknik Penerbangan Indonesia Curug, 2025)
Driven by the growing demand for seamless in-flight internet access and efforts to enhance passenger comfort, airlines are increasingly adopting in-flight connectivity technologies such as the Starlink Wi-Fi system. Integrating these systems into aircraft requires obtaining Supplemental Type Certificate (STC) approval from aviation authorities to ensure compliance with airworthiness standards. This paper examines the certification process for installing Starlink Wi-Fi on A320 aircraft under EASA and DGCA regulations, with a focus on airworthiness aspects. The process involves defining the design description, classifying the modification, and identifying the certification basis and compliance requirements. The installation is classified as a non-significant major change under both regulatory frameworks, requiring adherence to specific certification basis, Means of Compliance, and Design Organization Approval (DOA) frameworks. DGCA mandates Class C and D DOA, while EASA employs a single DOA structure based on approved privileges, highlighting distinct regulatory approaches to certification.